Out of the Curricular Shadows: Revolutionizing Undergraduate Immunology Education - Bruns, Heather A.; Deaver, Jill; Justement, Louis B. (Frontiers in Immunology, 2019)
Immunology has its developmental roots in understanding protection of the host from pathogens, leading to the development of vaccines and subsequently identification of soluble and cellular components of the immune system. Thus, immunology education has historically been tightly linked to infectious disease. Decades of research have demonstrated that the complexity and intricacies of the immune system are far greater than perhaps was once imagined. As a system that interfaces with all other organ systems in the body, it plays a key role in both maintaining health and causing life-threatening disease, thereby solidifying its importance in several clinical specialties beyond protective immunity. In the past decade, tremendous advances have taken place in which scientists and physicians have begun to harness the power of the immune system to create immunotherapies to fight cancer, inflammatory syndromes and other life-threatening diseases. Thus, the argument can be made that training individuals in the field of immunology is becoming increasingly important. However, immunology is a highly conceptual discipline and understanding how the multiple cellular and soluble components of the immune system work in concert requires knowledge in a number of disciplines, including molecular biology, cell biology, genetics, and biochemistry. Time is needed for students to process, evaluate, and apply this information in meaningful ways. Concomitantly, knowledge in the field of immunology is expanding rapidly, bolstering the need for increased time in the curriculum to facilitate the ability of educators to convey information so that it can be effectively understood and applied. We propose that it is time for a renaissance in immunology education at the undergraduate level to better prepare individuals who will subsequently pursue careers in medicine, related health professions, and research. The purpose of this article is to discuss the current state of undergraduate immunology education with respect to its prevalence and how this compares to other biological disciplines, the need to develop robust immunology curricula at the undergraduate level and the importance of such programs in preparing students for pursuing postgraduate training in the health professions, and research-intensive careers.